2004
DOI: 10.1590/s1519-566x2004000200003
|View full text |Cite
|
Sign up to set email alerts
|

Estimative of Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) development time with non linear models

Abstract: Estimativa do Tempo de Desenvolvimento de Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae)Através de Modelos Não Lineares RESUMO -O objetivo deste estudo foi avaliar a precisão dos modelos não lineares de Davidson (1942Davidson ( , 1944, Stinner et al. (1974), Sharpe & DeMichele (1977) PALAVRAS-CHAVE: Asopinae, controle biológico, Alabama argillacea, taxa de desenvolvimento, predador ABSTRACT -The objective of this study was to evaluate the precision of the non linear models of Davidson (1942Davidson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
0
20
1
2
Order By: Relevance
“…46 However, in the present study the Stinner model adequately described the development rates of different instars of H. foeniculi, with R 2 values higher than 0.71. For the aphid A. pomi, values of R 2 higher than 0.98 were obtained when the Stinner model was used.…”
Section: Sharpe and Demichelecontrasting
confidence: 50%
See 2 more Smart Citations
“…46 However, in the present study the Stinner model adequately described the development rates of different instars of H. foeniculi, with R 2 values higher than 0.71. For the aphid A. pomi, values of R 2 higher than 0.98 were obtained when the Stinner model was used.…”
Section: Sharpe and Demichelecontrasting
confidence: 50%
“…The same models also predicted R 2 values close to or higher than 0.90. The Sharpe and DeMichele and Lactin-2 models were also found to be good fits for Alabama argillacea (Hübner) (Lepidoptera: Noctuidae) 46 and its predator Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae). 47 Ramalho et al 48 also observed high R 2 values when using these two models for the parasitoid Bracon vulgaris Ashmead (Hymenoptera: Braconidae).…”
Section: Sharpe and Demichelementioning
confidence: 83%
See 1 more Smart Citation
“…Among these species are P. maculiventris and Perillus bioculatus (Fabricius) in North America and Europe, and Podisus nigrispinus (Dallas) in South America (Medeiros et al, 2004). Podisus nigrispinus is one of the most common species of Asopinae studied in the Neotropical region (De Clercq, 2000), and has been reported in several countries of South and Central America (Thomas, 1992;Medeiros et al, 2004;Lemos et al, 2005) as an important biological control agent in different crops. Although P. nigrispinus is one of the most studied species, there is still little information on its feeding behavior when submitted to different quantities of prey.…”
Section: Introductionmentioning
confidence: 99%
“…A temperatura tem papel crucial na vida dos insetos, podendo afetar seu desenvolvimento, sobrevivência e reprodução (SILVEIRA NETO et al, 1976;SOGLIA et al, 2002SOGLIA et al, , 2003SILVA, 2004;MEDEIROS et al, 2004) e, conseqüentemente, influenciar sua dinâmica populacional e sua capacidade de causar danos às plantas cultivadas. Os insetos somente podem alcançar a fase adulta e se reproduzir dentro de um gradiente de temperatura, existindo uma temperatura ótima.…”
unclassified